2012
DOI: 10.5539/jas.v4n10p35
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Effects on Corn Soil-plant-water Continuum in Alfisols of Southern Ohio

Abstract: Tillage alters soil physical properties and impacts soil water regime, crop's relative water content (RWC), and root distribution. Thus, a field study was conducted to characterize and correlate root distribution and assess RWC of corn (Zea mays L.) with soil physical properties under two tillage systems i.e. no-till (NT), and conventional tillage (CT). The RWC, determined four times during a course of the day at two growth stages (V8, i.e. 60 days after planting; and R2, i.e. 90 days after planting), was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
2
2
Order By: Relevance
“…In particular, for clayey red soil in the humid sub-tropical region, DP and CT treatments increased soil water content in the severe drought treatments: they were helpful in relieving drought stress impacts on the maize crop in favour of maintaining yield. This result is inconsistent with that in semi-arid soils, where shallow-till or NT rather than deep-till has been reported to increase soil moisture (Castellini & Ventrella 2012;Kahlon et al 2012). Nevertheless, this result has been supported in recent studies.…”
Section: Discussioncontrasting
confidence: 79%
“…In particular, for clayey red soil in the humid sub-tropical region, DP and CT treatments increased soil water content in the severe drought treatments: they were helpful in relieving drought stress impacts on the maize crop in favour of maintaining yield. This result is inconsistent with that in semi-arid soils, where shallow-till or NT rather than deep-till has been reported to increase soil moisture (Castellini & Ventrella 2012;Kahlon et al 2012). Nevertheless, this result has been supported in recent studies.…”
Section: Discussioncontrasting
confidence: 79%
“…On the contrary, no-till (NT) significantly decreased θ. However, this result is inconsistent with some reports in arid and semi-arid regions (Kahlon et al, 2012;Aziz et al, 2013;TerAvest et al, 2015). Salem et al (2015) reported that the highest soil θ was recorded under no-till in central Spain.…”
Section: Discussioncontrasting
confidence: 62%
“…Soil disturbance and tillage frequency decreases volumetric water content (Hussain et al, 1998). As in this study, the increase in soil moisture with depth was also reported by Dao (1993); Kahlon et al (2012); Kebede and Bekelle (2008).…”
Section: Discussionsupporting
confidence: 62%